Impaired network organization in mild age‐related hearing loss - Zhaopeng Tong; Chunhua Xing; Xiaomin Xu; Jin‐Jing Xu; Yuanqing Wu; Richard Salvi; Xindao Yin; Fei Zhao; Yu‐Chen Chen; Yuexin Cai (MedComm)
Abstract Age‐related hearing loss (ARHL) is considered one of the most common neurodegenerative disorders in the elderly; however, how it contributes to cognitive decline is poorly understood. With resting‐state functional magnetic resonance imaging from 66 individuals with ARHL and 54 healthy controls, group spatial independent component analyses, sliding window analyses, graph‐theory methods, multilayer networks, and correlation analyses were used to identify ARHL‐induced disturbances in static and dynamic functional network connectivity (sFNC/dFNC), alterations in global network switching and their links to cognitive performances. ARHL was associated with decreased sFNC/dFNC within the default mode network (DMN) and increased sFNC/dFNC between the DMN and central executive, salience (SN), and visual networks. The variability in dFNC between the DMN and auditory network (AUN) and between the SN and AUN was decreased in ARHL. The individuals with ARHL had lower network switching rates than controls among global network nodes, especially in the DMN. Some disturbances within DMN were associated with disrupted executive and memory performance. The prolonged loss of sensory information associated with ARHL‐induced compensatory within‐network segregations and between‐network integrations in the DMN might reduce network information processing and accelerate brain aging and cognitive decline.